Patient satisfaction after lower limb replantation surgery for traumatic amputation - a qualitative study - Yantao Pei; Yakubu Ibrahim; Gang Wang; Yuliang Sun; Benjamin Tze Keong Ding; Qingjia Xu (BMC Musculoskeletal Disorders, 2024)
Abstract Background The majority of published literature clinically assesses surgical outcomes after lower limb replantation for traumatic amputations. However, patients’ satisfaction and quality of life may not be accurately measured through rigid scoring using standardized patient reported outcome measures. Purpose The aim of this study was to qualitatively assess patient satisfaction and factors associated with achieving good outcomes after successful lower limb replantation surgery. Methods A semi-structured interview was conducted with 12 patients who underwent lower limb replantation surgery following traumatic amputation injuries. The interview focused on the patients’ experience and satisfaction throughout their injury, surgical journey, rehabilitation and reintegration into their communities. An inductive and deductive thematic analysis was applied using the recorded transcripts to evaluate the overall satisfaction of the patients after lower limb replantation surgery. Results The following observations emerged from the structured themes among all the patients interviewed: (1) Family and social support was significantly associated with improved qualities of life and satisfaction after lower limb replantation; (2) Patients were generally satisfied with their outcomes despite limitations in physical capabilities; (3) Satisfaction was associated with acceptance of their cosmetic deformity; (4) Social integration and being able to participate in a meaningful manner was associated with greater satisfaction after recovery. Conclusions Patients who undergo lower limb replantation can have a significantly improved quality of life if they have strong social support, are able to contribute in a meaningful manner to their communities after surgery, and are accepting of their cosmetic deficiencies.